Evaluation of the Operational CMEMS and Coastal Downstream Ocean Forecasting Services During the Storm Gloria (January 2020) - Sotillo, Marcos G.; Mourre, Baptiste; Mestres, Marc; Lorente, Pablo; Aznar, Roland; García-León, Manuel; Liste, Maria; Santana, Alex; Espino, Manuel; Álvarez, Enrique (Frontiers in Marine Science, 2021)
Storm Gloria was the 10th named storm in Europe for the 2019-2020 winter season, and it severely affected Spain and France. This powerful storm represents an excellent study case to analyze the capabilities of the different ocean model systems available in the Spanish Mediterranean coasts to simulate extreme events, as well as to assess their suitability to enhance preparedness in maritime disasters with high impacts on coastal areas. Five operational ocean forecasting services able to predict the storm-induced ocean circulation are evaluated. Three systems are delivered by CMEMS: the global scale solution, the specific Mediterranean basin scale one , and the regional solution for the Atlantic façade. Moreover, two higher resolution models focused on more limited areas: the WMOP system developed at SOCIB with a horizontal resolution of roughly 2 km and the PdE SAMOA systems with a 350-m resolution that cover coastal domains of the Spanish Port Authorities of Barcelona, Tarragona, Castellón and Almeria. Both the WMOP and SAMOA models are nested in CMEMS regional systems (MED and IBI, respectively). The skill of these 5 models in reproducing the surface dynamics in the area during Gloria is evaluated using in-situ measurements from numerous buoys and coastal meteorological stations as a reference to track the effects of the storm in essential ocean variables throughout January 2020. Modelled surface dynamics are validated against hourly surface current fields from the 2 high-frequency radar systems available (the SOCIB HF-Radar system covering the eastern part of the Ibiza Channel and the PdE one at Tarragona, which covers the Ebro Delta, one of the coastal areas most impacted by Gloria). The results assess the performance of the dynamical downscaling at two different levels: first, within the own CMEMS service (with their regional products, as enhanced solutions with respect to the global one) and second in the coastal down-streaming service side (with very high-resolution models reaching coastal scales). This multi-model study case focused on storm Gloria has allowed to identify some strengths and limitations of the systems currently in operations, and it can help outlining future model service upgrades aimed at better forecasting extreme coastal events.